Antibiotic use: a cross-sectional study evaluating the understanding, usage and perspectives of medical students and pathfinders of a public defence university in Malaysia - Haque, Mainul; A. Rahman, Nor Azlina; McKimm, Judy; Sartelli, Massimo; Mohammad Kibria, Golam; Islam, Md Zakirul; Lutfi, Siti Nur Najihah; Othman, Nur Syamirah Aishah; Abdullah, Shahidah Leong (MDPI AG, 2019)
Antimicrobial prescribing behaviors are often influenced by the local culture and prescribing appropriateness of medical doctors and other health care professionals. Globally, Antimicrobial utilization practices have a profound impact on antimicrobial resistance and are a tremendous public health concern. The aim of this survey was to explore the knowledge and attitudes of medical students from the National Defence University of Malaysia regarding antimicrobial usage and antimicrobial resistance. Research design and methods: This was a cross-sectional study. The study population consisted of undergraduate medical students in each year group from the National Defence University of Malaysia. Students receive limited formal training on the use of antibiotics in their curriculum, and most of this learning is opportunistic whilst on clinical placement. Universal sampling was used as the study population was small. Data were collected utilizing a previously validated instrument regarding antibiotic use. Simple descriptive statistics were used to generate frequencies and percentages with SPSS V21. This research was approved by the Centre for Research and Innovation Management, National Defence University of Malaysia. Results: 206 questionnaires were distributed with a response rate of 99.03%, 54% (110) male, and 46% (94) female. Out of the respondents, 65% (132) had used antibiotics in the last year. Respondents displayed a moderate level of knowledge about antibiotics. Conclusions: This study revealed that the older the student was, or when the year of study and total knowledge score was higher, the students were less likely to stop antimicrobials when they felt better or use leftover antibiotics without consulting a doctor. Therefore, the nearer the students were to graduation, the better their knowledge and skills were, and this translated into their own behaviors regarding use of antimicrobials. This finding has clear implications for curriculum design and the inclusion of formal teaching throughout the medical program on antimicrobial use and antimicrobial resistance (AMR). However, more research is needed on this topic, including the prescribing habits and antibiotic use of practicing doctors.